Beyond inspiratory muscle strength: Clinical utility of single-breath work capacity assessment in veterans with COPD. (February 2019) - Formiga, Magno F.; Vital, Isabel; Urdaneta, Gisel; Campos, Michael A.; Cahalin, Lawrence P.
Abstract: Background: Inspiratory muscle function in COPD has been traditionally described in terms of maximal inspiratory pressure (MIP). Arguably, however, is the day-to-day relevance of MIP, given that individuals rarely need maximal inspiratory forces to perform general tasks, but rather repeated breathing muscle contractions which demand endurance. The sustained maximal inspiratory pressure (SMIP) reflects the ability of the respiratory muscles to maintain force over time (i.e. single-breath work capacity). We investigated the relationships between SMIP and COPD-related clinical outcomes, hypothesizing that SMIP would have superior correlational and discriminatory value when compared to MIP. Methods: 61 males with mild-to-very severe airflow obstruction underwent measures of spirometry, whole-body plethysmography, symptomatology, comorbidity, quality of life, exacerbations and mental health. MIP and SMIP were obtained via the Test of Incremental Respiratory Endurance. Results: The mean ± SD MIP and SMIP were 77.2 ± 22.9 cmH2 O and 407.9 ± 122.8 PTU. Both MIP and SMIP positively correlated with pulmonary function, with SMIP displaying the highest correlations. We found significant differences in spirometry, hyperinflation, symptomatology, exacerbation frequency, comorbidity, quality of life and anxiety in subjects grouped as having reduced or normal single-breath work capacity. Finally, significantly lower SMIP values were found in individuals with an IC/TLC ratio ≤25%. Conclusions: The assessment of SMIP appears to have superior clinical value than MIP in COPD. Our analyses revealed that subjects whose SMIP was reduced experienced more severe airflow obstruction, greater hyperinflation, as well as worse health and mental status with increased symptomatology and impaired quality of life. Highlights: SMIP seems to have superior clinical value than the traditional measure of MIP in COPD. Subjects with reduced single-breath work capacity exhibited more severe symptomatology. Poorer SMIP values were associated with significantly worse health and mental status. Better quality of life and pulmonary function were found in subjects with normal SMIP. Significantly lower SMIP values were found in subjects with an IC/TLC ratio ≤25%.